Zambia Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank Group (World Bank, Washington, DC, 2018)
The government of Zambia is implementing the seventh National Development Plan (NDP) focused on building a diversified and resilient economy for sustained growth and social economic development (2017 – 2021). This second Zambia report on the Observance of Standards and Codes – Accounting and Auditing (ROSC A and A) is aimed at determining reforms that will further strengthen the accountancy profession to accelerate its contribution towards economic and social development. The report is set out as follows. Section I describes the objective, approach, country and economic context, and link between corporate and financial reporting and the seventh NDP, World Bank country partnership strategy, and different sectors; section II provides an assessment of the framework supporting the accountancy profession; section III discusses the status of implementation of 2007 policy recommendation; and section IV lists policy recommendations.